Pelaksanaan Good Corporate Governance (GCG) dalam Perseroan Terbatas (Lex Jurnalica, 2010)
Good Corporate Governance (GCG) or good corporate governance. GCG is very important for the company. With the implementation of GCG, the management company will run efficiently and effectively, so the impact on, namely: The size of the gains the company, whether or not the Great will be experienced by the company risks that could result in losses, Guaranteed least effective production in the company, and to maintain continuity and kontiniutas effort. The principles of good corporate governance, namely the principle of fairness (justice), transparency (Transparency), accountability (accountability), pertanggungajawaban (responsibility), independency (independen-cy), equality and fairness (fairness), while the implementation of Good Corporate Governance (GCG), the system decision-making by GCG in the Limited Liability Company, Penghindaraan conflict of interest (conflict of interest) shareholders, commissioners and directors. Writing method used is the juridical normative, while the techniques of collecting data obtained from the research literatureÂ Keywords: Implementation, Good Corporate Governance, Limited Liability